Increasing ethical decision making through flexible work arrangement - Zalafi, Zahratika; Sjabadhyni, Bertina; Suyanto, Helmi (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2019)
When faced with a particular ethical dilemma, individuals are expected to make ethical decisions through an ethical decision-making process (EDM). Today’s employees provide added value to organizations that implement flexible arrangements to support employee’s well being and work-life balance. This research was conducted through an online survey on 236 active employees with a minimum age of 22 years old in Indonesia. Likert scales were used to examine the effect of flexible work arrangements (FWA) mediated by work-life balance (WLB) on the level of EDM of individuals in organizations. The mediation results showed that FWA mediated by WLB significantly predicted an increase in individual’s EDM level (b = .359, SE = .116, 95% CI = .152 - .607). Positive implementation of FWA leads to balanced WLB which in turn increased the level of individual EDM.